Analysis of grain tribology and improved grinding temperature model based on discrete heat source. (February 2023) - Liu, Mingzheng; Li, Changhe; Zhang, Yanbin; Yang, Min; Gao, Teng; Cui, Xin; Wang, Xiaoming; Li, Haonan; Said, Zafar; Li, Runze; Sharma, Shubham
Abstract: A high grinding temperature will cause thermal damage to a workpiece surface and deterioration of surface integrity, which is the bottleneck of grinding. The present grinding temperature theoretical model is based on grain homogeneity and the continuous heat source distribution in the grinding zone. However, the random change in interference between the effective grains and a workpiece during the machining process causes a change in the grain tribological properties, resulting in varying transient grinding temperatures. Based on the current situation, the grain tribological mechanism and an improved temperature model based on a discrete heat source are proposed to reveal the temperature variation law of a workpiece in an actual grinding process. First, the surface topography model of a grinding wheel is established based on the geometric characteristics of grains, and the determination mechanism of effective grains is revealed. Furthermore, the interference mechanical behavior of the grains and workpiece is analyzed according to the kinematic law of grains in the sliding, plowing, and cutting stages. The mechanical model and specific grinding energy model at different stages are established, and the thermal distribution mechanism of effective grains is revealed. Finally, a temperature field mathematical model of a discrete heat source is established, and numerical simulation is performed to demonstrate the dynamic temperature change process of different grains. A new experimental method for measuring temperature at different positions of the workpiece with a bipolar thermocouple array is designed, and a regional numerical simulation and experimental temperature comparison method is innovatively proposed. Experimental results show that the grinding temperature measured under different cutting depth conditions is in good agreement with the numerical results, and the variation law is consistent. The minimum error in 64 groups of experimental measuring and numerical calculation comparison zones can reach 4.9%, and the proportion of zones with errors less than 10% can approach 86%. This study will provide a theoretical basis for the accurate suppression of workpiece surface thermal damage and the development of precision grinding in engineering discipline and machinery industry.